Composite web services to support travel information searching - Koo, Lee Chun; Liew, Pui Fong; Katuk, Norliza (2013)
This paper explains our preliminary study on a composite web services model for travel- based websites.The aim of the model is to provide a generic design for incorporating travel information in websites to assist travellers in searching relevant information over the Internet.The preliminary study explores generic features of travel-based websites as well as additional information that travellers always looking for such as currency and weather information, and local map. The approach that we used in this model is to merge difference web services into a single service that can be embedded in travel -based websites. We developed a prototype named QUICK Travel Assistant to demonstrate the model.